Life next to a landfill: urban marginality, environmental injustice and the Roma - Škobla, Daniel; Filčák, Richard (Race & class, 2024)
The site known as Lipnica is a segregated Roma settlement built on the edge of a municipal landfill in the district town of Turčany, central Slovakia (fictitious names have been used for the site and the town). The settlement emerged as a result of processes rooted in neoliberal economic restructuring, accompanied by a sharp rise in unemployment in the 1990s. The settlement was originally built to provide temporary housing for those who were in arrears for rent in municipal flats, and originally consisted of one apartment building and several modular cabins. In the following years it expanded, and today it is an ethnic quasi-ghetto for approximately 400 Roma inhabitants. From a theoretical perspective, an analysis of the Lipnica settlement is situated at the intersection of critical race theory and environmental justice theory. In this article, we describe the trajectory leading to the formation of the settlement and analyse how the impoverishment of the Roma, coupled with the construction of the community as ‘maladjusted’ anti-social others, facilitated their spatial exclusion. We conclude that the case demythologises culturising explanations for the emergence of Roma settlements, by using empirical data to show how Lipnica developed as a result of intentional discriminatory policies of the local ruling class used against an ethnic minority.